1996
DOI: 10.1063/1.869049
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative experimental and numerical investigation of a vortex ring impinging on a wall

Abstract: A joint experimental and computational methodology is developed and applied to investigate a vortex ring impinging normally on a wall. The method uses digital particle image velocimetry to make planar flow measurements, which are then used to initialize a second-order finite difference calculation. The experiment and the simulation are compared at later times and agree extremely well. The ring undergoes two rebounds from the wall and continues to expand. During the approach to the wall, peak vorticity grows by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…Some studies have investigated the flow field associated with the collision of the jet on a flat surface. Among the most notable, we can mention Cerra and Smith (1983), Orlandi and Verzicco (1993) and Fabris et al (1996). Ho and Nosseir (1981) revealed a feedback phenomenon, which can control the jet at the nozzle exit for high-speed subsonic impinging jets.…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have investigated the flow field associated with the collision of the jet on a flat surface. Among the most notable, we can mention Cerra and Smith (1983), Orlandi and Verzicco (1993) and Fabris et al (1996). Ho and Nosseir (1981) revealed a feedback phenomenon, which can control the jet at the nozzle exit for high-speed subsonic impinging jets.…”
Section: Introductionmentioning
confidence: 97%
“…1 The mechanism has revealed particular features that make the vortex ring a realistic candidate to enhance heat transfer from small electronic devices. A simplified situation involving this collision mechanism has been reported by other authors providing important insight on vortex stretching [2][3][4] and pressure gradients 4,5 at the wall, where the vortex core could be responsible for local and peaked shear stresses. 6 The interaction can be explained with the aid of the schematic sequence shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…High velocity gradients between the vortex ring and the flow near the wall are observed, and thus making a better mixing process by this interaction. For instance, Fabris et al 2 in a joint experimental-numerical investigation found that the peak vorticity grows about 50% by vortex stretching. Orlandi et al 3 made numerical simulations, where peak vorticity of the boundary layer near the wall increases abruptly as the ring approaches the wall, eventually leading to boundary layer separation even at moderately high Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Using initial vorticity fields from the DPJV measurement, Figure 5 (d) shows a much better agreement with experiments. It is interesting to note that without such novel experiments, the whole validity of the DNS code used for this simulation might have ended in doubt for a wrong reason (Liepmann and Dommermuth, 1991 ;Fabris et al , 1995). Also, it has to be mentioned that such experiments open new opportunities for interactive computational/experimental methods to be developed for thermo fluid flows (Humphrey et al , 1991).…”
Section: Journal Of Fluids Engineeringmentioning
confidence: 99%
“…Fig. 5 A comparative study of DNS simulation based on initial conditions from a model or DPIV vorticity distribution (Liepmann and Dommermuth 1991 ;Fabris et al, 1995) Experiments are essential in resolving modeling issues, such as boundary conditions, where modeling errors can produce errors in the solution of order one. The problem of defining the proper in-flow (upstream) condition and the determination of the dimensions of the computational box (blockage effect and correlation lengths) can easily benefit from appropriate laboratory simulation of the flow condition.…”
Section: Journal Of Fluids Engineeringmentioning
confidence: 99%